2007
DOI: 10.1089/neu.2006.0165
|View full text |Cite
|
Sign up to set email alerts
|

End-to-Side Nerve Repair in Peripheral Nerve Injury

Abstract: In peripheral nerve injury, end-to-side neurorrhaphy has been reported as an alternative in cases that the proximal nerve stump is not accessible. Several hypotheses have been proposed to explain peripheral nerve regeneration after end-to-side neurorrhaphy. Recent evidence suggests that nerve regeneration occurs by collateral sprouting. Although a great number of humoral factors have been identified, molecular mechanism of nerve regeneration after end-to-side neurorrhaphy has not been completely clarified yet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 64 publications
2
31
0
1
Order By: Relevance
“…2,16,17,21,24 In the study with the largest number of patients published to date, the author reported good results * Axillary nerves or musculocutaneous nerves were reconstructed with different donor nerves. MN = median nerve; NA = not applicable; RN = radial nerve; SSN = suprascapular nerve; UN = ulnar nerve.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…2,16,17,21,24 In the study with the largest number of patients published to date, the author reported good results * Axillary nerves or musculocutaneous nerves were reconstructed with different donor nerves. MN = median nerve; NA = not applicable; RN = radial nerve; SSN = suprascapular nerve; UN = ulnar nerve.…”
Section: Discussionmentioning
confidence: 97%
“…We use this method as our standard technique because studies with experimental models have indicated that the success rate of such sutures is high. 2,8,22 The existence of collateral sprouting of axons is well documented. Some authors have demonstrated in experimental studies that terminolateral nerve repair can be used without a surgical incision into the donor nerve's perineurium or epineurium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 While several articles demonstrate good results of end-toside neurorrhaphy in humans, 10,16 others do not suggest its indication. 17,18 For example, Fernandes et al 9 , after reviewing literature, affirmed the nonexistence of sufficient experimental or clinical evidence for the indication of end-to-side neurorrhaphy in humans. The same opinion is shared by Pienaar et al 4 , Pannicucci et al 11 and Beris et al 17 Due to the extremely favorable and tempting concepts of endto-side neurorrhaphy and of the significant difference of opinions in literature, the performance of new experimental studies with the addition of neurotrophic factors is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Functional motor and sensory reinnervation of target tissue was observed after such nerve repair in experimental mammals. [7][8][9][10][11][12][13][14][15][16] Also, several clinical case series suggest that some patients with extensive nerve injuries in the upper extremity, facial palsy, or neurinoma could benefit by such a treatment, although the results are quite unpredictable.…”
Section: Introductionmentioning
confidence: 99%